Light Controls Cytokinin Signaling via Transcriptional Regulation of Constitutively Active Sensor Histidine Kinase CKI1 - Dobisova, Tereza; Hrdinova, Vendula; Cuesta, Candela; Michlickova, Sarka; Urbankova, Ivana; Hejatkova, Romana; Zadnikova, Petra; Pernisova, Marketa; Benkova, Eva; Hejatko, Jan (Plant physiology, 2017)
In plants, the multistep phosphorelay (MSP) pathway mediates a range of regulatory processes, including those activated by cytokinins. The cross talk between cytokinin response and light has been known for a long time. However, the molecular mechanism underlying the interaction between light and cytokinin signaling remains elusive. In the screen for upstream regulators we identified a LONG PALE HYPOCOTYL (LPH) gene whose activity is indispensable for spatiotemporally correct expression of CYTOKININ INDEPENDENT1 (CKI1), encoding the constitutively active sensor His kinase that activates MSP signaling. lph is a new allele of HEME OXYGENASE1 (HY1) that encodes the key protein in the biosynthesis of phytochromobilin, a cofactor of photoconvertible phytochromes. Our analysis confirmed the light-dependent regulation of the CKI1 expression pattern. We show that CKI1 expression is under the control of phytochrome A (phyA), functioning as a dual (both positive and negative) regulator of CKI1 expression, presumably via the phyA-regulated transcription factors (TF) PHYTOCHROME INTERACTING FACTOR3 and CIRCADIAN CLOCK ASSOCIATED1. Changes in CKI1 expression observed in lph/hy1-7 and phy mutants correlate with misregulation of MSP signaling, changed cytokinin sensitivity, and developmental aberrations that were previously shown to be associated with cytokinin and/or CKI1 action. Besides that, we demonstrate a novel role of phyA-dependent CKI1 expression in the hypocotyl elongation and hook development during skotomorphogenesis. Based on these results, we propose that the light-dependent regulation of CKI1 provides a plausible mechanistic link underlying the well-known interaction between light- and cytokinin-controlled plant development.
Keywords: proteiny huseníčku; mutace; fytochrom A; Arabidopsis; signální transdukce; hemová oxygenasa (decyklizující); proteinkinasy; Arabidopsis Proteins; Models, Genetic; Phytochrome A; Cytokinins; regulace genové exprese u rostlin; Signal Transduction; světlo; Heme Oxygenase (Decyclizing); cytokininy; hypokotyl; Plants, Genetically Modified; Protein Kinases; Gene Expression Regulation, Plant; modely genetické; Hypocotyl; geneticky modifikované rostliny; Mutation; Light